2009
DOI: 10.4049/jimmunol.0902274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Flavin Mononucleotide Module Residue Critical for Activity of Inducible Nitrite Oxide Synthase

Abstract: Inducible NO synthase (iNOS) contains an amino-terminal oxygenase domain, a carboxy-terminal reductase domain, and an intervening calmodulin-binding domain. For the synthesis of NO, iNOS is active as a homodimer formed by oxygenase domains, while the reductase domain is required to transfer electrons from NADPH. In this study, we identify glutamate 658 in the FMN domain of human iNOS to be a critical residue for iNOS activity and we explore the underlying mechanism for such role. Mutation of glutamate to aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Azithromycin when combined with Riboflavin elicits the function of macrophage but lower in comparison to Riboflavin when combined to Fluroquinolone signaling [36]. In our study pre-treatment of macrophages with antibiotics does not lead to residual toxic effects on macrophages, and the effects are due to changes in response to live cells because in our results by FACS analysis of ROS a significant increase in ROS production on addition of antibiotic CIP was documented which cannot be attributed by dead cells.…”
Section: Discussionmentioning
confidence: 46%
“…Azithromycin when combined with Riboflavin elicits the function of macrophage but lower in comparison to Riboflavin when combined to Fluroquinolone signaling [36]. In our study pre-treatment of macrophages with antibiotics does not lead to residual toxic effects on macrophages, and the effects are due to changes in response to live cells because in our results by FACS analysis of ROS a significant increase in ROS production on addition of antibiotic CIP was documented which cannot be attributed by dead cells.…”
Section: Discussionmentioning
confidence: 46%
“…In that work, a neutralization mutation at the nNOS FMN domain surface was shown to increase NO synthesis activity by enhancing the rate of [Fe(II)−NO] oxidation. Another study showed that FMN domain residue E658 is important for human iNOS activity and also suggested the importance of the FMN module for such activity . These results indicate the importance of appropriate docking of the FMN domain for both efficient IET and substrate−heme interactions.…”
Section: Discussionmentioning
confidence: 88%
“…2). The striking detail and recognizable repeating shapes in the 2D averages allowed for immediate assignment of domains based on silhouette and size information provided by known mammalian NOS domain crystal structures (8,(14)(15)(16)21). The central ellipsoid density is the dimerized NOS oxidase domain; the C-shaped density is the FAD/NADPH subdomain; the circular density typically bound within the C-shaped density is the FMN subdomain; the other circular density positioned between the reductase and oxidase domains is CaM bound to the CaM-binding helix of NOS (Fig.…”
Section: Resultsmentioning
confidence: 99%